A convergent growth approach to electroactive ferrocene rich carbosilane- and siloxane-based dendrons, dendrimers, and dendronized polymers. Issue 17 (6th April 2023) - Bruña, Sonia; Perles, Josefina; Cuadrado, Isabel
Abstract : A convergent growth approach to ferrocenyl-rich dendritic macromolecules based on carbosilane and siloxane skeletons, which act as electrode modifiers. Abstract : The construction of the first members of a novel family of structurally well-defined, ferrocenyl rich, dendritic macromolecules based on carbosilane skeletons and siloxane linkages has been achieved via a convergent growth approach. Starting from triferrocenylvinylsilane Fc3 SiCHCH2 (1 ) (Fc = Fe(η 5 -C5 H4 )(η 5 -C5 H5 ) as the key monomer, the sequential utilization of platinum-catalyzed hydrosilylation and alkenylation steps with Grignard reagents (allylmagnesium bromide) can be applied to prepare three different branched structures: multiferrocenyl-terminated dendrons 2 and 3, dendrimers 4 and 5, and dendronized polymers 7n –9n . All of the dendritic metallomacromolecules have been thoroughly characterized using a combination of elemental analysis, multinuclear ( 1 H, 13 C, 29 Si) NMR spectroscopy, FT-IR and MALDI-TOF mass spectrometry, to establish their chemical structures and properties. The molecular structures of G1 -dendron 3 and dendrimer 4, containing six and nine ferrocenyl units, respectively, have been successfully determined by single-crystal X-ray analysis, compound 4 being the branched multiferrocenyl-containing siloxane with the highest number of Fc substituents whose structure has been reported so far. Electrochemical studies (using cyclic voltammetry (CV) and square wave voltammetry (SWV) performed in dichloromethane solution with [PF6 ] − and [B(C6 F5 )] 4− as supporting electrolyte anions of different coordinating abilities) reveal that all the macromolecular compounds obtained exhibit a three-wave redox pattern, suggesting appreciable electronic interactions between the silicon-bridged triferrocenyl moieties as they are successively oxidized. In addition, dendrimer 5 and dendronized polymers 7n –9n, with 12 and 4 < n < 14 ferrocenyl units, respectively, linked in threes around the periphery, undergo remarkable oxidative precipitation in CH2 Cl2 /[ n -Bu4 N][PF6 ] and are able to form chemically modified electrodes with stable electroactive films.